2020
DOI: 10.1021/acs.est.9b06764
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Sulfate in the Photochemical Renoxification on Real PM2.5

Abstract: The active nitrogen species (HONO, NO, and NO2) have important impacts on the atmospheric oxidative capacity and the transformation of many atmospheric species. In this study, a fast photochemical renoxification rate of adsorbed HNO3/NO3 – to active nitrogen species (HONO, NO, and NO2) was detected on real urban PM2.5, and sulfate was found to play a key role in this process. Different from the reported direct photolysis pathway, the photochemical reaction of HNO3/NO3 – on PM2.5 is dominated by a photosensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Moreover, significant differences between EF values obtained from field studies and laboratory studies indicate a complex process of pNO3 photolysis that may be influenced by various environmental parameters, e.g., the aerosol pNO3 loading and the aerosol composition (Bao et al, 2018(Bao et al, , 2020Ye et al, 2016Ye et al, , 2017, and experimental laboratory conditions, e.g., collected particles on the filter or generated airborne particles (Shi et al, 2021;Wang et al, 2021). We, therefore, suggest that this process still needs further field or laboratory constraints.…”
Section: Constraint On Hono Formation From the Photolysis Of Particulate Nitratementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, significant differences between EF values obtained from field studies and laboratory studies indicate a complex process of pNO3 photolysis that may be influenced by various environmental parameters, e.g., the aerosol pNO3 loading and the aerosol composition (Bao et al, 2018(Bao et al, , 2020Ye et al, 2016Ye et al, , 2017, and experimental laboratory conditions, e.g., collected particles on the filter or generated airborne particles (Shi et al, 2021;Wang et al, 2021). We, therefore, suggest that this process still needs further field or laboratory constraints.…”
Section: Constraint On Hono Formation From the Photolysis Of Particulate Nitratementioning
confidence: 99%
“…The photolysis of particulate nitrate (pNO3) was found to be an important HONO source in low NOx areas such as forest canopy and marine boundary layer. High enhancement factors (EF = J(pNO3)/J(HNO3)), within the range of tens to thousands, were proposed in forest area, marine boundary layer, and polluted areas like the NCP (Bao et al, 2020;Ye et al, 2016Ye et al, , 2017Zhou et al, 2007Zhou et al, , 2011. However, model studies with field constraints (Romer et al, 2018;Xue et al, 2020) found that the EF was moderate (7-30) rather than tens to thousands obtained in laboratory studies (Bao et al, 2020;Ye et al, 2016Ye et al, , 2017Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reed et al, 2017). Some researchers have suggested that deposited NO 3 − and HNO 3 can be recycled back to gas phase NO x under illumination, via the renoxification process (Schuttlefield et al, 2008;Romer et al, 2018;Bao et al, 2020;Shi et al, 2021b). Photolytic renoxification occurs under light with a wavelength of < 350 nm, through the photolysis of NO 3 − /HNO 3 adsorbed on the solid surface to generate NO x .…”
Section: Introductionmentioning
confidence: 99%
“…in the atmosphere has received extensive attention over the past several years, and the nitrate photolysis frequency (Jnitrate) is still argued. In the laboratory studies, some researchers (Bao et al, 2018;Ye et al, 2016Ye et al, , 2017 showed that nitrate photolysis was an important HONO source, the measured Jnitrate was 1-3 orders larger than the gaseous nitric acid (HNO3) photolysis frequency (JHNO3) and could reach up to 10 -4 s -1 , and a number of substances including humic acid (Yang et al, 2018), sulfate (Bao et al, 2020) and TiO2 (Xu et al, 2021) might enhance the reaction significantly; while Shi et al (2021) found that the Jnitrate/JHNO3 ratio was <10 when using suspended submicron particulate sodium and ammonium nitrate rather than PM2.5 samples. In the field studies combining with model simulations, Kasibhatla et al (2018) compared NOx observations in Cape Verde Atmospheric Observatory with GEOS-Chem (Goddard Earth Observing System-Chemistry) model simulations and reported a Jnitrate/JHNO3 ratio of 25-50, Romer et al (2018) reported a Jnitrate/JHNO3 ratio of < 30 based on observations of NOx (= NO + NO2) and HNO3 over the Yellow Sea and a box model simulation.…”
Section: Introductionmentioning
confidence: 99%